Pengembangan Bahan Ajar E-Modul Menggunakan Web Canva Pada Pembelajaran IPAS di Kelas IV Sekolah Dasar - Fitri, Azmi Ruzani Ulfa; Ariani, Yetti (Universitas Negeri Padang, 2023)
The research is motivated by the fact that there is a lack of use of technology in making teaching materials in schools. Even though there are adequate facilities for the manufacture of teaching materials. This study aims to develop teaching materials using the Canva web for science learning that is valid and practically applicable to the learning process. This type of research is development research (R&D) with the ADDIE model: analysis, design, development, implementation, and evaluation. Data for this study were obtained from validation sheets and response questionnaires and analyzed using quantitative data analysis and expressed qualitatively. The validation sheet consists of material expert validation sheets, language, media and driving teachers. While this response questionnaire consists of teacher and student response questionnaires. The test subjects for this study were 24 people, consisting of 11 male students and 13 female students in grade IVB SDN 10 Bandar Make Padang city. The results of this study obtained teaching materials in the form of valid and practical e-modules. The overall validation results obtained a percentage of 93.25% in the